Analisis Cacat Kempos Pada Produk Cup dengan Metode Failure Modes and Effects Analysis (Studi Kasus di Salah Satu Perusahaan Plastic and Printing di Sidoarjo, Jawa Timur) - Adhi Setya Hutama; Bayu Airlangga Zainudin2 (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
Percentage of problems in the cup production process, then we need an appropriate method to find the root cause of the cause of the note. One of the methods used in this study to reduce defects in the cup production process is using the FMEA (Failure Mode and Effect Analysis) method. FMEA identifies the critical causes of defects by conducting a risk assessment so that the risk priority of the failure mode is known. The risk assessment consists of the severity of the effects of a failure mode (severity), the frequency of occurrence of failures (occurrence), and the controls used to detect failures (detection). These priorities are developed and actions are formulated to be implemented to reduce risks so that it can be seen where preventive actions will be useful to prevent defects from occurring. Based on the results of the analysis using the Failure Mode and Effects Analysis (FMEA) method, it was found that the factor causing the defect based on the highest Risk Priority Number (RPN) value was a deflated bottom cup defect with the cause of potential failure being O-ring down holder wear so that failure was only detected after there was damage.